Motivating and demotivating factors and self-efficacy of EFL university teachers after the Covid-19 pandemic : a case study at Universidad del Valle (2024)
ABSTRACT: Motivation has been considered as one of the factors that affect teachers’ practices, performance and self-efficacy. During the Covid-19 pandemic, many language teachers faced challenges that affected their motivation and language teaching practices, including the lack of technology, online teaching and the lack of academic and mental health support. However, little is known about teacher motivation after the Covid-19 pandemic. It is unclear how teachers overcame difficult situations or changed their practices and how their motivation and self-efficacy was affected by the new normality. Investigating teacher motivation after the pandemic is important to identify the factors that motivate and demotivate language teachers and their view of self-efficacy (i.e. performance and practices) after transitioning from virtual teaching to face-to-face and hybrid interactions. This qualitative case study, therefore, investigated the motivating and demotivating factors and self-efficacy of a group of 22 EFL teachers at Universidad del Valle after the Covid-19 Pandemic. The study adopted Dörnyei and Ushioda (2011) and Ryan and Deci’s (2000) model and categories of motivation to identify which factors influenced language teacher motivation at their workplaces after the Covid-19 pandemic. Data were collected through a closed-ended questionnaire administered online to 22 lecturers and a follow-up semi-structured interview with 10 lecturers. Qualitative data were analyzed using content analysis. Findings indicate that intrinsic factors, such as teaching vocation, interest in ongoing learning, self-esteem, and pleasure and satisfaction of teaching, along with extrinsic factors, such as face-to-face interactions, and flexibility in teaching methods, motivated these teachers after the pandemic. Conversely, extrinsic factors, such as heavy workloads, lack of mental health support, and limited support from and relationship with colleagues were demotivating. Student feedback and attitude towards the class appeared as being motivating for some teachers and demotivating for others. Additionally, teachers believe there is a strong relationship between motivation and self-efficacy, and that it can be positively or negatively affected by feedback and relationships with students and academic staff and the teachers’ critical view of their own work. However, this factor does not hinder the quality of education they provide, in their view. These findings suggest that social interactions and vocation during the post-pandemic helped EFL lecturers maintain their motivation. From these findings we can conclude that while intrinsic factors are crucial for sustaining motivation, supportive extrinsic conditions are also essential for an optimal teaching environment. These findings suggest that validation from colleagues and students, teachers’ self-perception, and motivation are important to be effective at work. Even though motivation has an important role in teachers’ perceptions of self-efficacy, it is not the only factor that affects their performance and the overall quality of education. The findings of this investigation are relevant to our context and other similar contexts because they contribute to our understanding of the intrinsic and extrinsic factors that influenced EFL university teachers after the Covid-19 pandemic, particularly in our research context. If teachers are motivated, they might have a positive impact on their teaching practices and their students’ learning. Implications of this study’s findings are discussed in regard to the strategies needed to increase teacher’s motivation at their workplace after the Covid-19 pandemic.